Isolation of a thermostable alkaline protease producing bacterial strain and kinetic studies on the enzyme - Anpalagan, De.V. (My University, 2013)
Abstract: This study focuses on the isolation and identification of alkaline protease producing bacteria and the enzyme production by the selected bacteria. For this purpose bacterial strains were isolated from dog (61Nos), beef (17Nos) and fish (14Nos) decaying soil. Single colonies of the isolated bacterial strains were purified by repeated streaking and cultivating in nutrient-agar medium at 40oC for 24h. Among the 92 bacterial strains, selected 36 strains produced alkaline protease activity, above 4 UmL-1.Among the 36 alkaline protease producers, 4 strains which gave alkaline protease activity in the range from 35 to 54 UmL-1 (DDS2, DDS21, DDS33 and DDS47) were selected.Based on the morphological and biochemical tests isolates DDS2, DDS21, DDS33 and DDS47were identified as Bacillussubtilis, Bacillusthuringiensis, Bacillus laterosporusand Bacillus cereus respectively. To select the best alkalineproteases produced by B.thuringiensis,B. subtilis,B. laterosporusand B.cereus were characterized and they showed zero order kinetics up to 10, 15, 10 and 15min respectively.Among the selected isolatesB. SubtilisandB. cereus produced alkaline proteasewith optimum pH of 10.5 for the activity, while the protease produced byB. thuringiensisand B. laterosporusshowed optimum pH of 9.5. Thus B. subtilisandB. cereus were selected andB. subtilisproduced highest alkaline protease and its protease showed highest activity at72oC and pH 10.5 and good thermostability (Half life-48 min) without additives.The optimized culture conditions for B. subtilis were 370C, the fermentation medium to flask volume ratio 1 : 20, inoculum size 17% (v/v) of 18h old inoculum from 36h old slant culture and agitation speed of 200rpm and fermentation time was 92h. The optimization studies increased the protease production by 2.1 foldwhile the time taken to produce highest protease activity was reduced by 28h. Optimization of fermentation medium was studied. Calcium free medium was found to be best for protease production. MgSO4.7H2O of 0.35gL-1gave highest growthat 24 hours and protease activity at 92h and 15gL-1NaCl and0.1gL-1ZnCl2were most suitable for protease production. Optimization of peptone as 8gL-1 and yeast extract as 8gL-1improved the protease production by 1.08 and 1.12 folds respectively. When the peptone and Yeast extract were replaced withdifferent nitrogen sources such as (NH4)2SO4, soyabean, casein, beef extract, tryptone, milk powder and malt milk powder,tryptone 25gL-1was more effective in improvingalkaline protease production from Bacillus subtilis [887 (±6.9)UmL-1]. Among the tested nitrogen sources,tryptone was selected as the best nitrogen source for highest alkaline protease production.Therefore 1.9 foldincrease in protease activity was achieved after optimizing the concentration of the best nitrogen source. Among the carbon sources used(sucrose malt extract and starch) glucose was more effective for alkaline protease production [987.3(±6.9) UmL-1].By the optimization of culture conditions and culture medium the protease production was improved by 12.6 fold. Based on the properties of the protease produced by B. subtilis, the enzyme can be used in industries regarding alkaline proteases.